From Micro Gravitational Waves to the Quantum Indeterminism - Thuan, Vo Van (Communications in Physics, 2015)
An attempt to search for the links b etween general relativity and quantum mechanics is prop osed which bases on an extended space-time symmetry. A simplified cylindrical mo del of gravitational geometrical dynamics leads to a micro geo desic description of strongly curved space-time which implies a duality b etween quantum mechanical equations and the emission law of a sp ecific mo de of micro gravitational waves.